2012
DOI: 10.1186/2251-7715-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Compost' leachate recycling through land treatment and application of natural Zeolite

Abstract: Purpose In a novel approach, certain organic wastes byproducts of agro industries were assessed for their ability to support maize growth and Zn bioavailability in maize grain. Methods In a field experiment, maize (Zea mays) was supplemented with farm yard manure (FYM), press mud (PM), fisheries manure (FM), and slaughter house waste (SHW) in combination with Zn soil application (ZnS) and Zn foliar spray (ZnF) with recommended doses of N:P:K (140:100:60 kg ha −1 ), respectively. Besides assessing the maize gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The framework of zeolite contains various channels and cavities where cations and water molecules are located. The channel structure of zeolites acts as a molecular sieve for selective cation exchange (Tabatabaei et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The framework of zeolite contains various channels and cavities where cations and water molecules are located. The channel structure of zeolites acts as a molecular sieve for selective cation exchange (Tabatabaei et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Isfahan region, Iran, municipal and industrial treated wastewater used as a water resource or irrigation of different production (Tabatabaei et al 2012). So, it is more necessary to select the best and new irrigation techniques with the management to improve efficiency of irrigation system (Najafi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the combination of electrodialysis and willow field is appropriate for treating RO concentrate. Tabatabaei et al (2012) investigated the clinoptilolite abilities on decreasing chemical and biological index of the compost factory's leachate. …”
mentioning
confidence: 99%